2022
DOI: 10.1038/s41598-022-07471-2
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-eluting cobalt–chrome alloy stent suppresses stent-induced tissue hyperplasia in a porcine Eustachian tube model

Abstract: Various preclinical studies with developed Eustachian tube (ET) stents are in progress but have not yet been clinically applied. ET stent is limited by stent-induced tissue hyperplasia in preclinical studies. The effectiveness of sirolimus-eluting cobalt–chrome alloy stent (SES) in suppressing stent-induced tissue hyperplasia after stent placement in the porcine ET model was investigated. Six pigs were divided into two groups (i.e., the control and the SES groups) with three pigs for each group. The control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The shape of the stent can also be altered by movements surrounding the ET in a living animal, such as swallowing and chewing 4 , 5 . Previous studies reported that the distal end of the stent collapsed because of the insertion of a cobalt–chrome stent 13 , 14 , 17 . Therefore, the T-SEMS and C-SEMS were fabricated with nitinol, a self-expandable metal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of the stent can also be altered by movements surrounding the ET in a living animal, such as swallowing and chewing 4 , 5 . Previous studies reported that the distal end of the stent collapsed because of the insertion of a cobalt–chrome stent 13 , 14 , 17 . Therefore, the T-SEMS and C-SEMS were fabricated with nitinol, a self-expandable metal.…”
Section: Discussionmentioning
confidence: 99%
“…In a human cadaver study, stents with different diameters were inserted and evaluated; however, all stents were not fully dilated at the distal cartilaginous portion 18 . Additionally, a commercially available coronary cobalt–chrome stent was implanted in the ET of sheep and pigs and subsequently evaluated 13 , 14 , 17 . In this study, a T-SEMS made of self-expanding nitinol wire was optimized for the ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical feasibility and safety of cobalt-chrome alloy stent placement via a minimally invasive approach under endoscopic guidance have been reported. However, stent-induced tissue hyperplasia caused by mechanical injuries remains a significant obstacle to a successful stent placement [ 10 , 11 ]. Drug-eluting stents loaded with antiproliferative agents have been investigated to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-eluting stents loaded with antiproliferative agents have been investigated to overcome these limitations. Recently, a sirolimus-eluting stent successfully prevented stent-induced tissue hyperplasia in the porcine ET model [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%